PENGARUH LITERASI KEUANGAN DIGITAL DAN AKSES KEUANGAN DIGITAL TERHADAP KINERJA UMKM KOTA SEMARANG - Rokhimah, Zulaika Putri (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
The digital economy has become increasingly popular since the COVID 19 pandemic. Business activists are competing to utilize technology that can create greater business opportunities. The use of technology creates a business system that can be utilized by everyone, including micro, small and medium enterprise (MSME) owners. This research wants to know the influence of digital financial literacy, digital financial access and how it affects the performance of MSMEs in Semarang City. The research method used is quantitative. The sample in this research is MSMEs registered in Semarang City. The data collection used was by distributing questionnaires and the results obtained were 89 respondents. The research instrument test used was SmartPLS 3. The results obtained were that digital financial literacy and digital financial access had an effect on the performance of MSMEs. And digital financial access has been proven to play a role in mediating the relationship between digital financial literacy and MSME performance.